ANALISIS PERBANDINGAN NILAI KELAS PAGI DAN KELAS MALAM MATA KULIAH AKUNTANSI PAJAK MATERI TAX AMNESTY - Wulandari, Endang (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
This research is entitled Comparative Analysis of the Values ??of Morning Class and Evening Class for Tax Accounting Subjects on Tax Amnesty. The problem raised in this research is this research entitled Comparative Analysis of the Values ??of Morning Class and Evening Class for Tax Accounting Courses on Tax Amnesty Materials. The purpose of this study is to test that there is no difference in the value of the Tax Accounting course whose material contains Tax Amnesty between the morning regular class students and the evening regular class students. The research method is using the average difference test hypothesis test. The results of the discussion above are known t0>t?=>t0=2.27>t?= -1.318 then H0 is accepted because there is no difference in the value of the morning class and evening class, and H1 is rejected because t0 > t?, from the results of the statistical test calculations above, it turns out that there is no difference the value between the morning class and the evening class, and the hypothesis that the morning class is less valuable than the evening class is rejected, because the results of the calculation show that the average test for the morning class is greater than the evening class.